2D Ruddlesden-Popper perovskite ferroelectric film for high-performance, self-powered and ultra-stable UV photodetector boosted by ferro-pyro-phototronic effect and surface passivation. (November 2022) - Guo, Linjuan; Qi, Yaqian; Yang, Zheng; Zhao, Lei; Zhang, Wei; Wang, Xinzhan; Liu, Haixu; Yan, Guoying; Wang, Shufang; Pan, Caofeng
Abstract: 2D Ruddlesden-Popper (RP) perovskites have attracted enormous attention in optoelectronic fields compared with their 3D counterparts. However, most of the reported perovskite ferroelectrics-based self-powered photodetectors (PDs) are fabricated from bulk single crystals rather than perovskite thin films with improved reproducibility, flexibility, and less preparation time. Nevertheless, the defect sites at surfaces and grain boundaries of 2D perovskites polycrystalline films make them vulnerable to humidity. Herein, the highly crystallized 2D RP perovskite ferroelectric films are successfully obtained. Then, a passivation method is applied on 2D perovskite film by an in-situ reaction with 4-fluoro-phenylethylamine iodide (4-FPEAI), which reduces the defect sites and endows the perovskite films with the outstanding hydrophobic property. Then, the as-prepared 2D-perovskite ferroelectric thin films were fabricated into self-powered PDs. Boosted by the ferro-pyro-phototronic effect, the self-powered PDs demonstrate excellent optoelectronic performances at 360 nm, with dark current less than 1 × 10 −12 A, a peak responsivity over 1 A W −1, a detectivity of 1.5 × 10 14 Jones and fast response/recovery speed. The photoresponsivity and specific detectivity are both enhanced by 67.8 times regarding the relative peak-to-peak current, compared with those only based on the photovoltaic induced photocurrent. Further, the PDs show high stability towards high humidity and thermal treatment. Graphical Abstract: Herein, the highly crystallized 2D RP perovskite ferroelectric films are successfully obtained. Then, a passivation method is applied on 2D perovskite film by an in-situ reaction with 4-fluoro-phenylethylamine iodide, which reduce the defect sites and endow the perovskite films with the outstanding hydrophobic property. Then, the as-prepared 2D-perovskite ferroelectric thin films were fabricated into self-powered photodetectors (PDs). Boosted by the ferro-pyro-phototronic effect, the self-powered PDs demonstrate excellent optoelectronic performances at 360 nm, with dark current less than 1 × 10 −12 A, a peak responsivity over 1 A W −1, a detectivity of 1.5 × 10 14 jones and fast response/recovery speed. The photoresponsivity and specific detectivity are both enhanced by 67.8 times regarding the relative peak-to-peak current, compared with those only based on the photovoltaic induced photocurrent. The PDs show high stability towards high humidity and thermal treatment. ga1 Highlight: 2D RP perovskite ferroelectric films are demonstrated for ferro-pyro-phototronic effect based-self-powered UV photodetector.